Characterization of Molybdenum-Vanadium Oxide Catalyst Prepared By Homogeneous Precipitation Method Using Urea Hydrolysis - Woi, Pei Meng (2007)
Molybdenum-vanadium oxide (Mo-V-O) has been constantly reported as an active and selective catalyst for the direct propane transformation to acrylic acid. In this study, crystalline molybdenum-vanadium oxide catalysts have been successfully synthesized by homogeneous precipitation method using urea hydrolysis. A new approach was taken whereby the solid obtained were further refluxed in the presence of additives which are adipic acid (AA), maleic acid (MA) and polyvinyl alcohol (PVA). The precursors which upon drying were subjected to various calcination temperatures. The effect of additives and calcination temperatures on the formation and properties of Mo-V-O characteristics were monitored by Thermogravimetric Analysis (TGA), Powder X-ray diffraction (XRD), Photon Cross Correlation Spectroscopy (PCCS), Inductively Couple Plasma-Atomic Emission Spectroscopy (ICP-AES), BET Surface Area Measurements (SBET), Scanning Electron Microscopy (SEM) and Hydrogen-Temperature Programmed Reduction (H2-TPR). It was found that without the presence of additives, the precursor was in a semicrystalline form of ammonium molybdate anorthic phase. However, in the presence of additives, the precursors were highly crystalline with the presence of desirable orthorhombic, monoclinic and tetragonal MoVOx species. Heat treatment that imposed on the materials has successfully transformed the precursor into a more stable phase. The desirable orthorhombic phase was found to be achieved when sample was calcined at 873 K in nitrogen atmosphere. SEM analysis showed a rather randomly distributed particle with defined size and shape. Total surface area, SBET for sample prepared by complexing MoV salts with PVA (MoVPVA873) was found to be the highest, i.e. 20.5 m2 g-1. This property consequently contributed to the highest total amount of oxygen species removed from the oxide, hence an indication of the highly active and selective characteristics borne by the oxide. This is further confirmed by catalytic test of propane oxidation to acrylic acid which done on the sample. The test showed that samples treated with organic species (AA, MA, PVA) give better acrylic acid selectivity and yield.